PENGARUH MODEL COOPERATIVE LEARNING TIPE INQUIRY TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA - RAHMAT, PUPU SAEFUL; Setiawan, Iyan; Novitasari, Adissa Dwi; Parida, Parida (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2023)
AbstractThe problem of this research was the low learning outcomes of students in class X  SMAN I Kuningan. The purpose of this study was focused on 3 (three) things, including: (1) to find out the differences in motivation and learning outcomes of students in the pre-test between a classe used cooperative learning model of inquiry type compared to a classes used conventional learning methods; (2) to find out the differences in students' motivation and learning outcomes on the post test  between a class using  inquiry type cooperative learning model compared to a class using conventional learning methods; (3) to find out the difference in the increase in motivation and learning outcomes (pre-test and post-test measurements) between a class using the inquiry-type cooperative learning model compared to a class using conventional learning methods. The research used experimental method. Data was collected through a written test (pre-test and post-test). The subjects of this study were class X1 (28 people) and X2 (28 people). To analyze the research data, the t-test was used. Based on the results of data analysis, it was concluded: (1) there was no difference in motivation and learning outcomes of students in the pre-test between the experimental class and the control class, meaning that before treatment using the inquiry-type cooperative learning model, they had the same initial ability  (no difference); (2) there is no difference in the motivation and learning outcomes of students on the final test (post test) between the experimental class compared to the control class, meaning that after giving treatment using the inquiry type cooperative learning model, the effectiveness of learning has not been able to improve student learning outcomes at the end learning; (3) there was difference in motivation and learning outcomes (pre-test and post-test measurements) between the experimental class compared to the control class.  Keywords: Inquiry type cooperative learning model; learning motivation; learning outcome. AbstrakPenelitian ini didasarkan pada rendahnya hasil belajar siswa kelas X.SMAN I Kuningan. Tujuan penelitian ini difokuskan pada 3 (tiga) hal, antara lain:  (1) untuk mengetahui perbedaan motivasi dan hasil belajar siswa  (pre test) antara kelas yang menggunakan model cooperative learning tipe inquiry dibanding dengan kelas yang menggunakan metode pembelajaran konvensional; (2) untuk mengetahui perbedaan motivasi dan hasil belajar siswa (post test) antara kelas yang menggunakan model cooperative learning tipe inquiry dibanding dengan kelas yang menggunakan metode pembelajaran konvensional; (3) untuk mengetahui perbedaan peningkatan motivasi dan hasil belajar (pre test dan post test) antara kelas yang menggunakan model cooperative learning tipe inquiry dibanding dengan kelas yang menggunakan metode pembelajaran konvensional.  Metode yang digunakan dalam penelitian ini adalah metode eksperimen. Pengumpulan data dilakukan melalui tes tertulis (pre test dan post test). Subjek penelitian ini adalah kelas X1 (28 orang) dan X2 (28 orang). Untuk menganalisis data hasil penelitian digunakan uji-t. Berdasarkan hasil analisis data diperoleh kesimpulan: (1) tidak terdapat perbedaan motivasi dan hasil belajarsiswa (pre test) antara kelas eksperimen dengan kelas kontrol, artinya sebelum perlakuan dengan menggunakan model pembelajaran kooperatif tipe inkuiri, siswa memiliki kemampuan awal yang sama (tidak ada perbedaan); (2) tidak terdapat perbedaan motivasi dan hasil belajar siswa (post test) antara kelas eksperimen dibanding dengan kelas kontrol, artinya sesudah pemberian perlakuan dengan menggunakan model pembelajaran kooperatif tipe inkuiri, efektivitas pembelajaran belum mampu meningkatkan hasil belajar siswa pada akhir pembelajaran; (3) terdapat perbedaan motivasi dan hasil belajar (pre test dan post test) antara kelas eksperimen dibanding dengan kelas kontrol.  Kata Kunci: Model cooperative learning tipe inquiry; motivasi belajar;  hasil belajar.